PENGARUH PENERAPAN MODEL PEMBELAJARAN BRAIN BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI DISPOSISI MATEMATIS SISWA SMA/MA - Ramadhanti, Oktarisa; Revita, Rena; Fitri, Irma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' mathematical communication skills are still considered not optimal. The purpose of this study was to analyze the differences in mathematical communication skills between students taught using the Brain Based Learning (BBL) model and those taught through conventional learning, the differences in mathematical communication skills based on the level of mathematical disposition, as well as the interaction effect between the learning model and mathematical disposition on the mathematical communication skills of senior high school students. This study employed a factorial experimental design with the population consisting of all tenth-grade students of SMA Negeri 1 Reteh. The sample was selected using the cluster random sampling technique, resulting in class X.6 as the experimental class and class X.5 as the control class. Data were collected through tests, questionnaires, observations, and documentation using instruments in the form of a mathematical communication skills test, a mathematical disposition questionnaire, learning observation sheets, as well as photographs and other supporting documents. Data were analyzed using a two-way ANOVA test. The results showed that there was a difference in mathematical communication skills between students taught using the BBL model and those taught through conventional learning. In addition, there were differences in mathematical communication skills based on the level of mathematical disposition. However, there was no interaction effect between the learning model and mathematical disposition on students' mathematical communication skills. Therefore, the BBL model affects the mathematical communication skills of senior high school students when viewed in terms of their mathematical disposition.